Experiences of facilitators and barriers for fulfilment of human needs when living with restless legs syndrome: a qualitative study - Elzana Odzakovic; Monika Allgurin; Lise-Lotte Jonasson; Sandra Öberg; Bengt Fridlund; Martin Ulander; Jonas Lind; Anders Broström (International Journal of Qualitative Studies on Health & Well-Being)
Purpose Restless Legs Syndrome (RLS) is a widespread condition that affects sleep leading to daytime sleepiness, depression, and reduced quality of life. This study aims to determine and describe how patients with RLS experience their everyday life, with a focus on facilitators and barriers related to Maslow’s hierarchical theory of human needs. Method Semi-structured interviews were analysed with qualitative content analysis resulting in facilitators and barriers affecting the fulfilment of the five human needs. Results Addressing RLS symptoms through medications and a quiet sleep environment fulfils psychological needs. Control over RLS symptoms, engagement in activities, trust in treatments, and social support meet safety and security needs. Social inclusion, close relationships, and meaningful interactions fulfil a sense of belongingness and love needs despite RLS. Competence in managing RLS, effective self-care strategies, confident communication, and trust-building support esteem needs. Finally, comprehensive understanding through person-centred interventions and coping fulfils the self-actualization needs in managing RLS. Conclusion Holistic and person-centred interventions, including facilitators for the fulfilment of physiological, psychological, and social needs could help healthcare professionals to provide holistic care.